Circumscribing communities: Marine conservation and territorialization in southeastern Tanzania. Issue 100 (March 2019) - Raycraft, Justin
Highlights: The MBREMP constitutes an inconsistent/contested process of territorialization. The park extends the state apparatus to a rural locality on its geographic and political periphery. Park management undermines villagers' customary rights and constrains local livelihoods. Barriers to territorialization exist in practice. Circumscription of coastal communities creates new sociopolitical terrains of territoriality. Abstract: The Mnazi Bay-Ruvuma Estuary Marine Park (MBREMP), a multiple-use marine protected area in southeastern Tanzania, is publicly framed as a project that benefits coastal villagers and marine biodiversity. In reality, villagers are politically excluded from park governance, though geographically included inside of park boundaries. While the stated aim of the park is to protect the ecological integrity of the marine environment, I argue that the MBREMP constitutes a contested and inconsistent process of territorialization characterized by boundary-making, zoning, and regulating resource-use inside of a geographically-defined area. Through the Marine Parks and Reserves Unit, the park extends the reach of the state apparatus to a rural locality that would otherwise be situated on its geographic and political periphery. However, disconnects exist between territorialization on paper and in practice due to the on-the-ground politics of conservation. Practical management constraints, political complexities related to state-private partnerships, and bottom-up resistance create barriers to territorialization. Nonetheless, park management practices constrain local livelihoods and negatively impact villagers' everyday lives. The reclassification of Village Land as Reserve Land undermines customary rights to resources and renders customary occupancy rights ever more precarious. Citing their lived experiences of subjugation, some villagers perceive the park as a political instrument for securing state resource control. Rather than a 'fortress' model of conservation that physically displaces villagers, I maintain that circumscription of coastal communities creates new social and political terrains of territoriality.